ISA API: An open platform for interoperable life science experimental metadata. Issue 9 (16th September 2021) - Johnson, David; Batista, Dominique; Cochrane, Keeva; Davey, Robert P; Etuk, Anthony; Gonzalez-Beltran, Alejandra; Haug, Kenneth; Izzo, Massimiliano; Larralde, Martin; Lawson, Thomas N; Minotto, Alice; Moreno, Pablo; et al.
Abstract: Background: The Investigation/Study/Assay (ISA) Metadata Framework is an established and widely used set of open source community specifications and software tools for enabling discovery, exchange, and publication of metadata from experiments in the life sciences. The original ISA software suite provided a set of user-facing Java tools for creating and manipulating the information structured in ISA-Tab—a now widely used tabular format. To make the ISA framework more accessible to machines and enable programmatic manipulation of experiment metadata, the JSON serialization ISA-JSON was developed. Results: In this work, we present the ISA API, a Python library for the creation, editing, parsing, and validating of ISA-Tab and ISA-JSON formats by using a common data model engineered as Python object classes. We describe the ISA API feature set, early adopters, and its growing user community. Conclusions: The ISA API provides users with rich programmatic metadata-handling functionality to support automation, a common interface, and an interoperable medium between the 2 ISA formats, as well as with other life science data formats required for depositing data in public databases.